MolADI: A Web Server for Automatic Analysis of Protein–Small Molecule Dynamic Interactions - Bing Bai; Rongfeng Zou; H. C. Stephen Chan; Hongchun Li; Shuguang Yuan (Molecules, 2021)
Protein–ligand interaction analysis is important for drug discovery and rational protein design. The existing online tools adopt only a single conformation of the complex structure for calculating and displaying the interactions, whereas both protein residues and ligand molecules are flexible to some extent. The interactions evolved with time in the trajectories are of greater interest. MolADI is a user-friendly online tool which analyzes the protein–ligand interactions in detail for either a single structure or a trajectory. Interactions can be viewed easily with both 2D graphs and 3D representations. MolADI is available as a web application.